2021
DOI: 10.31925/farmacia.2021.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Analysis of Cannabidiol Orodispersible Formulations

Abstract: Cannabidiol (CBD) is an alkaloid that can be found in the Cannabis species, currently used in United States of America under the name of Epidiolex ® , which was approved by Food and Drug Administration (FDA) for seizures treatment. The purpose of this study was to investigate the structural characteristics of the raw materials and to compare 2 film formulations with different analytical methods. In order to differentiate the structural properties, the following methods were used: X-ray powder diffraction (XRPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The initiation of degradation was observed above 140 °C, which is in line with the TGA observations. The DSC endothermic peak at 68.97 °C for CBD-IS was also observed by Andriotis et al 21 and Vlad et al 22 According to the authors, CBD-IS decomposition might occur at temperatures higher than 300 °C. The melting of CBD-IS powder was measured to be 68.6 ± 0.2 °C which substantiated the TGA and DSC observations.…”
Section: Resultssupporting
confidence: 66%
“…The initiation of degradation was observed above 140 °C, which is in line with the TGA observations. The DSC endothermic peak at 68.97 °C for CBD-IS was also observed by Andriotis et al 21 and Vlad et al 22 According to the authors, CBD-IS decomposition might occur at temperatures higher than 300 °C. The melting of CBD-IS powder was measured to be 68.6 ± 0.2 °C which substantiated the TGA and DSC observations.…”
Section: Resultssupporting
confidence: 66%
“…As shown, our experimental values are numerically close to those from previous studies, indicating the accuracy of the DSC method. The differences might be related to the sample purity, though this is reported in only one of the previous works (ref ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have also studied the melting point and the enthalpy of fusion of CBD with DSC analysis, reporting values in the range of 67.5–71.3 °C and 19–28 kJ mol –1 , respectively. A comparison of the thermal analysis data for CBD that were collected in this study and those reported in previous works is provided in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic bands of CBD were identi ed at 3518 cm -1 , 3404 cm -1 , 1628 cm -1 , and 1585 cm -1 [21]. In the FT-IR spectrum of CBD, the prominent bands in the range of 3404 cm -1 to 3518 cm -1 corresponded to O-H stretching vibrations, while the bands at 3074 cm -1 represented C-H stretching (phenyl), the band at 2924 cm -1 indicated methyl and methylene groups, the band at 1585 cm -1 represented C = C stretching in the phenyl ring, and C-O stretching vibrations were observed at 1213 cm -1 [22].…”
Section: Ftir Analysismentioning
confidence: 99%